Effect of pineapple (Ananas Comosus) culture by- products on the enzymatic deproteinization of shrimp biowastes - Alpízar Cordero, Javier Rodrigo (2013)
The present work aims to a preliminary study of the deproteinization capacity of proteolytic extracts from pineapple biowastes in different concentrations as potential green process to treat by-products of the shrimp fishery in order to obtain chitin and chitosan. The proteolytic extract isolated from pineapple biowastes was obtained from pineapple stems using a sulfuric acid buffer solution. The proteolytic extract from pineapple was characterized according to its protein content, total sugars and enzymatic activity against a commercial bromelin standard and a negative control. Results indicate that applying a crude pineapple proteolytic extract succeeded in to eliminate up to 97% of the proteins present in a shrimp biowaste sample, being more active than any of its dilutions, in a 24 hours study. Our results suggest that pineapple biowastes can be consider as a potential green biosource to promote shrimp deproteinization, providing a biotechnological activity to the traditional chemical process involving sodium hydroxide. This novel methodology will provide new applications for pineapple biowastes and reduce costs and contamination during chitin and chitosan production.